Optimalisasi Layanan BK Berbasis Multikultural dalam Menanamkan Nilai Toleransi dan Kebhinekaan pada Gen-Z - Vinda Chairunnisa; Asbi Asbi (Pancasila and Civics Education Journal, 2026)
Abstract: The increasing diversity of social interactions in the digital era has created new challenges in fostering tolerance and appreciation of diversity among Gen-Z. Multicultural-based guidance and counseling services are needed as a strategic approach to strengthen the values of tolerance and diversity. This study aims to analyze the optimization of multicultural guidance and counseling services in fostering the values of tolerance and diversity among students. The study used a qualitative descriptive approach implemented on students of the Guidance and Counseling Study Program at Al-Washliyah Muslim Nusantara University (UMN) Medan. Participants were selected through purposive sampling technique. Data were collected through interviews, observation, and documentation, then analyzed using the Miles and Huberman interactive model. The results of the study indicate that multicultural-based guidance and counseling services play an important role in increasing diversity awareness, intercultural understanding, social empathy, and inclusive behavior of students. Optimization of services is carried out through multicultural information services, classical guidance, multicultural group counseling, cross-cultural dialogue, diversity project-based learning, and digital counseling. This research produced a conceptual model consisting of five stages: multicultural awareness, intercultural understanding, empathy development, value internalization, and inclusive behavior. This model contributes to developing students who are tolerant, inclusive, democratic, and oriented toward the values of diversity.Keywords: Multicultural Guidance and Counseling, Tolerance, Diversity, Generation ZAbstrak: Meningkatnya keberagaman interaksi sosial di era digital telah menciptakan tantangan baru dalam menumbuhkan toleransi dan apresiasi terhadap keberagaman di kalangan Gen-Z. Layanan bimbingan dan konseling berbasis multikultural dibutuhkan sebagai pendekatan strategis untuk memperkuat nilai-nilai toleransi dan keberagaman. Penelitian ini bertujuan untuk menganalisis optimalisasi layanan bimbingan dan konseling multikultural dalam menumbuhkan nilai toleransi dan keberagaman di kalangan Mahasiswa. Penelitian menggunakan pendekatan deskriptif kualitatif yang dilaksanakan pada mahasiswa Program Studi Bimbingan dan Konseling Universitas Muslim Nusantara (UMN) Al-Washliyah Medan. Partisipan dipilih melalui teknik purposive sampling. Data dikumpulkan melalui wawancara, observasi, dan dokumentasi, kemudian dianalisis menggunakan model interaktif Miles dan Huberman. Hasil penelitian menunjukkan bahwa layanan BK berbasis multikultural berperan penting dalam meningkatkan kesadaran keberagaman, pemahaman antarbudaya, empati sosial, dan perilaku inklusif mahasiswa. Optimalisasi layanan dilakukan melalui layanan informasi multikultural, bimbingan klasikal, konseling kelompok multikultural, dialog lintas budaya, pembelajaran berbasis proyek keberagaman, dan konseling digital. Penelitian ini menghasilkan model konseptual yang terdiri atas lima tahapan, yaitu multicultural awareness, intercultural understanding, empathy development, value internalization, dan inclusive behaviour. Model tersebut berkontribusi dalam membentuk mahasiswa yang toleran, inklusif, demokratis, dan berorientasi pada nilai-nilai kebhinekaan.Kata Kunci: Bimbingan dan Konseling Multikultural, Toleransi, Keberagaman, Generasi Z